No evidence for activated autophagy in left ventricular myocardium at early reperfusion with protection by remote ischemic preconditioning in patients undergoing coronary artery bypass grafting. - Nilgün Gedik; Matthias Thielmann; Eva Kottenberg; Jürgen Peters; Heinz Jakob; Gerd Heusch; Petra Kleinbongard (PLoS ONE)
Objective Remote ischemic preconditioning (RIPC) by repeated brief limb ischemia/reperfusion reduces myocardial injury in patients undergoing coronary artery bypass grafting (CABG). Activation of signal transducer and activator of transcription 5 (STAT5) in left ventricular (LV) myocardium at early reperfusion is associated with such protection. Autophagy, i.e., removal of dysfunctional cellular components through lysosomes, has been proposed as one mechanism of cardioprotection. Therefore, we analyzed whether or not the protection by RIPC is associated with activated autophagy. Methods CABG patients were randomized to undergo RIPC (3×5 min blood pressure cuff inflation/5 min deflation) or placebo (cuff deflated) before skin incision (n = 10/10). Transmural myocardial biopsies were taken from the LV before cardioplegia (baseline) and at early (5-10 min) reperfusion. RIPC-induced protection was reflected by decreased serum troponin I concentration area under the curve (194±17 versus 709±129 ng/ml × 72 h, p = 0.002). Western blotting for beclin-1-phosphorylation and protein expression of autophagy-related gene 5-12 (ATG5-12) complex, light chain 3 (LC3), parkin, and p62 was performed. STAT3-, STAT5- and extracellular signal-regulated protein kinase 1/2 (ERK1/2)-phosphorylation was used as positive control to confirm signal activation by ischemia/reperfusion. Results Signals of all analyzed autophagy proteins did not differ between baseline and early reperfusion and not between RIPC and placebo. STAT5-phosphorylation was greater at early reperfusion only with RIPC (2.2-fold, p = 0.02). STAT3- and ERK1/2-phosphorylation were greater at early reperfusion with placebo and RIPC (≥2.7-fold versus baseline, p≤0.05). Conclusion Protection through RIPC in patients undergoing CABG surgery does not appear to be associated with enhanced autophagy in LV myocardium at early reperfusion.